PENGARUH PEMBERIAN INFUSA CARICA PAPAYA TERHADAP NYERI DISMINORE PRIMER PADA MAHASISWA - Lely Aprilia (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2019)
Primary dysmenorrhea is a pain that occursduring menstruation, without any infection of thepelvis and without abnormalities in the genitals of thereal. Ideally, disminore is natural to be experiencedby adolescents, when disminore pain is categorizedas severe it will affect daily activities. Based on thepreliminary study results, 60 female universitystudents received primary disinfectant. The aim is toanalyze the effect of giving carica papaya infusion toprimary dismalore on Midwifery student. This research uses pre experimental designwith One group Pretest posttest Design approach.Independent variables are carica papaya infusa anddependent variable is primary disminore pain. Thepopulation of this research were 60 female studentswho suffered primary disinfecting and the sampleswere 16 respondents using non-probability samplingtechnique with accidental sampling technique.Instruments used in pain scale observation sheetswere analyzed using Paired Sample T-Test statistictest. Based on the results of the research beforegiving carica papaya infusa there are 16 studentswho experienced primary disminore and after giveninfusa carica papaya all students experienceddecreased pain scale disminore. Result of statisticaltest of Paired Sample T-Test, got pain scale pre andpost result got result p value <a or (0,000 <0,05) soHa accepted. This suggests that there is an effect ofdisminary pain scale between before and aftertreatment of carica papaya infusa. It is expected that female students whoexperience disminore pain to get used tononpharmacology therapy to reduce pain like one ofthem by drinking carica papaya infusa.